A photoacoustic patch for three-dimensional imaging of hemoglobin and core temperature - Xiaoxiang Gao; Xiangjun Chen; Hongjie Hu; Xinyu Wang; Wentong Yue; Jing Mu; Zhiyuan Lou; Ruiqi Zhang; Keren Shi; Xue Chen; Muyang Lin; Baiyan Qi; et al. (Nature Communications, 2022)
The authors present a wearable photoacoustic patch, which integrates laser diodes and piezoelectric transducers for three-dimensional imaging of hemoglobin and temperature in deep tissues.